Pendampingan Penggunaan Software Aplikasi Sebagai Pendukung Menjalankan Perilaku Hidup Sehat di Lingkungan Panti Asuhan Nurul Istiqomah Al Hira’ - Salam, Abu; Rakasiwi, Sindhu; Paramita, Cinantya; Supriyanto, Catur; Octaviani, Dhita Aulia; Mulyanto, Edy (LPPM UNIVERSITAS DIAN NUSWANTORO, 2025)
The Clean and Healthy Lifestyle Program (PHBS) is an important program to encourage the implementation of a healthy lifestyle in maintaining, preserving, and improving health. Many diseases can be avoided if the community implements a healthy lifestyle. PHBS is ideal for implementation in school-age children, because they are included in the group at risk for health problems due to several factors. Technology in education has been proven to significantly change the way interaction and learning in the classroom, more efficiently, more easily accessible, and can build the skills needed in the current digital era and in the future. The use of digital applications as one of the products of technology has been widely used in both health and education, and are interrelated with each other where they complement each other. Information on health problems certainly requires the field of education to convey it, and vice versa, education cannot run smoothly if the environment is unhealthy. Thus, the role of technology in both fields is very important. Based on the things mentioned above, it is necessary to provide knowledge to students about PHBS. In addition to being given knowledge, students also need to be given guidance when practicing the PHBS material and including the role of technology in the form of digital applications so that learning can be more enjoyable and effective, where previously it was necessary to conduct socialization and training first regarding the use of the application to the caretakers of the Islamic boarding school. Based on the reasons stated, this time the team took the initiative to hold an activity in the form of Community Service with the theme of PHBS Assistance for Students with Digital Application Socialization, with a predetermined location, namely at the Nurul Istiqomah Al Hira 'Islamic Boarding School, so that PHBS can become a habit for students in their daily lives and can transmit these good habits to their environment.